Oxidation behaviours of ZrB2-SiC-MoSi2 composites at 1800 °C in air with different pressures. (15th August 2019) - Yang, Yang; Li, Meishuan; Xu, Lin; Xu, Jingjun; Qian, Yuhai; Zuo, Jun; Li, Tongqi
Highlights: In 0.5 kPa air, catastrophic oxidation occurred for both ZrB2 -SiC and ZrB2 -SiC-MoSi2 composites. As the increase of air pressure, the substrate consumption was decreased in both composites. Oxidation resistance of ZrB2 -SiC composite was enhanced by adding MoSi2 in 5 and 10 air, with much smaller substrate consumption. MoSi2 could react with ZrB2 to form stable MoB, inhibiting the formation of volatile B2 O3 and causing a continuous SiO2 outer layer exist. Abstract: The oxidation behaviours of ZrB2 -20SiC and ZrB2 -20SiC-10MoSi2 (vol.%) at 1800 °C in air with different pressures of 0.5, 5 and 10 kPa (correspondingly the oxygen partial pressure was 0.1, 1 and 2 kPa, respectively) were investigated. In 0.5 kPa air, catastrophic oxidation occurred for both composites. However, the addition of MoSi2 could enhance the oxidation resistance of the ZrB2 -20SiC composite in 5 and 10 kPa air, this was attributed to the reactions of MoSi2 with ZrB2 and highly volatile B2 O3 to form stable MoB, causing the formation of a continuous, compact and silica-rich outer oxide layer with lower oxygen permeability.